PERAN HUTAN KOTA DALAM MEMPERBAIKI KUALITAS UDARA - AMBAR TRI RATNANINGSIH; ENI SUHESTI (Universitas Lancang Kuning, 2010)
ABSTRACTThe increase of motorized vechicles in the city has caused environmentproblem, especially the air pollution as the emission of gasses containing heavymetal. The Research was designed to know more optimal town forest function inaccomplishment of its function. This research aim to to : 1) to know measurement ofquality of air variables in various the form of urban forests in Pekanbaru city ,covering :dirt rate, jerapan and metal absorption, 2) to find the relation of form ofurban forest with quality of air, 3) to find the best form of urban forest in make up ofthe quality of air. Research is executed in 8 location, consist of 4 urban forest locationin form of line and 4 other location in form of ganging. Data which collected is dirtrate, and jerapan and metal absorption. Data which analyzed gathered descriptively.Result of research showed that there are influence or relationship of form of urbanforest with quality of air. Result of research showed that there are influence orrelationship of form of urban forest with quality of air. Urban forest influence thequality of air where type form of ganging forest will degrade dirt rate equal to 89,00g/m3 and permeate heavy metal of Pb, Cu, Fe and of Mn in comparison with formof line